ANALISIS EKONOMI DAN MANAJEMEN PERBAIKAN SISTEM USAHATANI NILAM DI DESA KABUPATEN BOMBANA SULAWESI TENGGARA (KASUS DI DESA BABAMOLINGKU) - Rustam Supendy (Universitas Tadulako, 2016)
Patchouli plantshave shown increasingly high production along with the income of their farmers compared to cacao plant. The research was conducted at an area of six ha in Babangmolingku village Bombana District from January to March 2016 involving 15 cooperation farmers which were compared to 15 non-cooperation farmers. There were three technology packages tested i.e. introduced technology based on such technology derived from the research results of the Balitro Institution, pioneer farmer technology, and farmer formula technology. The research results showed that the largest profit of IDR 35,923, 000 was generated by the farming system which adopted the introduced technology followed by the pioneer technology (IDR 15,639,000) and by the farmer formula technology (IDR 7,700,000). The patchouli farming system is feasible to be developed in Babamolingku village as shown by its B/C values of 3.88 for the first technology, 3.46 for the second technology and 2.4 for the third technology. Management functions should be taken into consideration for increasing oil production thus the benefit received by the farmers increase as well.Keywords:, Introduced Technology, Oil, Patchouli, and Pioneer Technology